Entrepreneurial marketing strategies of Born Globals: Multiple case studies of Swedish-based firms - Riss, Rosalie (My University, 2011)
The earlier international and global marketing literature has participated in expanding our understanding of the marketing strategies of large global firms, but little has been written particularly on the marketing strategies of born globals (BGs). Hence, international entrepreneurship emerged providing knowledge about the characteristics and performance drivers of BGs. However, research still lacks of studies exploring the factors influencing the choice of entrepreneurial marketing strategy of BGs, and further, which factors have the biggest impact on BG’s marketing performance. Therefore, this study aims to analyze the entrepreneurial marketing strategies of Swedish BGs and also, to discover which factors have the biggest impact on this development and performance. The analysis of Swedish cases through the two following dimensions will help gaining greater understanding of which entrepreneurial marketing strategies are right to reach higher performance: the innovativeness of marketing strategies and the adaptation of marketing strategies to countries or customers. The research was conducted through a qualitative study with interviewing the CEOs and Marketing Directors of four BGs based in Sweden. The data was collected in 2010 and 2011 and has partially for purpose to be compared to earlier research on Finnish BGs (as this study is partly a replication study initiated from previous research among Finnish BGs). The theoretical assumption developed within this study that Swedish BGs and Finnish BGs differ as to their entrepreneurial marketing strategy (regarded the dimensions of innovativeness and adaptation of marketing strategy) received support. The theoretical framework followed in this study provides new understanding of entrepreneurial marketing literature by examining entrepreneurial marketing in BGs and explaining the effects of global context on entrepreneurial marketing strategies.
Keywords: Entrepreneurial Marketing; Marketing Strategies; Born Globals; International Entrepreneurship; Innovativeness; Standardization/Adaptation.; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|